Komparasi Kemampuan Membaca Permulaan Anak Melalui Media Pembelajaran Montase - Rohani, Rohani; Puspitasari, Ratna Nila (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2023)
Beginning reading ability is the basis for further and fluent children's reading ability. Through observations conducted by researchers at PAS Ar-Rohim Kindergarten, researchers found that there were some children who still had initial reading abilities that were not in line with expectations, including 10 out of 13 children who still had difficulty recognizing letter symbols from A-Z, distinguishing words that had the same initial letter, and arranging letters to form a word. This study aims to find out whether there are differences in children's beginning reading abilities through montage learning media in group A of TK PAS Ar-Rohim Bancang Sambit Ponorogo. This study used a quantitative method of the pre-experimental type and the One Group Pretest Posttest design. Data collection was carried out through observation and tests. The research object came from the students of PAS Ar-Rohim Kindergarten selected by saturated sampling technique. The research data were then analyzed using the paired sample t-test and drawing conclusions. Data analysis in this study was processed and visualized with the help of SPSS 23. Based on the results of data analysis it was found that (1) in the experiments that had been carried out there were differences in children's initial reading ability before and after the montage activity was given. The children's initial reading ability before being given treatment obtained the pretest results with an average score of 19.6923 and after being given the treatment the results of the posttest were 30.5385. The difference between before and after the treatment was given was 10.84615. On the results of the paired sample t-test, the sig.(2-tailed) result is 0.00 <0.005, which means that Ho is rejected and Ha is accepted